Social sustainability of EU-approved voluntary schemes for biofuels: Implications for rural livelihoods - German, L.; Schoneveld, George C. (Center for International Forestry Research, 2011)
The rapid expansion of biofuel production and consumption in response to global climate mitigation commitments and fuel security concerns has raised concerns over the social and environmental sustainability of biofuel feedstock production, processing and trade. The European Union has thus balanced the commitment to biofuels as one of the options for meeting its renewable energy targets for the transport sector with a set of sustainability criteria for economic operators supplying biofuels to its member states. Seven voluntary ‘EU sustainability schemes’ for biofuels were approved in July 2011 as a means to verify compliance. While mandated sustainability criteria of the EU Renewable Energy Directive (RED) have a strong environmental focus, a number of these voluntary schemes have social sustainability as a significant component of their requirements for achieving certification. This paper evaluates the social sustainability of these schemes through a review of the substantive content and procedural rules of these schemes, and discusses its implications for rural livelihoods in producer countries. The absence of social sustainability provisions in several schemes, the limited scope of most other schemes and procedural rules providing compliance loopholes point to the urgent need to expand the scope of EU RED to safeguard rural livelihoods in the global South.